Masculinities in Play (Cham : Springer International Publishing, 2018)
This volume addresses the persistent and frequently toxic associations between masculinity and games. It explores many of the critical issues in contemporary studies of masculinity-including issues of fatherhood, homoeroticism, eSports, fan cultures, and militarism-and their intersections with digital games, the contexts of their play, and the social futures associated with sustained involvement in gaming cultures. Unlike much of the research and public discourse that put the onus of "fixing" games and gaming cultures on those at its margins-women, LGBTQ, and people of color-this volume turns attention to men and masculinities, offering vital and productive avenues for both practical and theoretical intervention.
1. Introduction: Masculinity and Gaming: Mediated Masculinities in PlayBy Nicholas Taylor & Gerald Voorhees -- 2. "We're Going to Have to Do Things that Are Unthinkable": Masculinity/Games/Torture (Derek Burrill) -- 3. Army Men: Military Masculinity in Call of Duty (Gregory Blackburn) -- 4. The End of the Dream? How Grand Theft Auto V Simulates and Subverts Its Male Player-Character Dynamics (Kyle Moody) -- 5. "You're A Hunter, Bro": Representations of Masculinity in Until Dawn (Rebecca Waldie) -- 6. (Re)Reading Fatherhood: Applying Reader Response Theory to Joel's Father Role In The Last Of Us (Mark Cruea) -- 7. He Scores Through a Screen: Mediating Masculinities through Hockey Video Games (Marc Ouellette and Steven Conway) -- 8. Militarism and Masculinity in Dungeons & Dragons (Aaron Trammell) -- 9. At the Intersection of Difficulty and Masculinity: Crafting the Play Ethic (Nicholas A. Hanford) -- 10. Orchestrating Difference: Representing Gender in Video Game Music (Michael Austin) -- 11. Tools of the Game: The Gendered Discourses of Peripheral Advertising (Sam Srauy and Valerie Palmer-Mehta) -- 12. Performing Neoliberal Masculinity: Reconfiguring Hegemonic Masculinity in Professional Gaming (Gerald Voorhees and Alexandra Orlando) -- 13. Masculinity's New Battle Arena in International E-Sports: The Games Begin (Lily Zhu) -- 14. Technomasculinity and its Influence in Video Game Production (Robin Johnson) -- 15. Not So Straight Shooters: Queering the Cyborg Body in Masculinized Gaming (Nicholas Taylor and Shira Chess).
Literature, Cultural and Media Studies
text file PDF
Keywords: Culture-Study and teaching; Communication; Sociology; United States-Study and teaching; Social media